2019
DOI: 10.1016/j.ijrobp.2019.06.451
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of Prophylactic Cranial Irradiation with or without Hippocampal Avoidance for SMALL-CELL LUNG Cancer

Abstract: Purpose/Objective(s): Clinical evidence suggests that radiation dose received by the hippocampus during whole brain radiotherapy may play a role in radiation-induced neurocognitive decline. To prospectively evaluate the neurocognitive (NC) benefit of hippocampal sparing (PCI-HA), we have developed a phase III clinical trial (PREMER) to test hippocampal sparing during PCI. Materials/Methods: 118 patients undergoing PCI were randomized to receive PCI (nZ60) or PCI-HA (nZ58). The hippocampus was contoured, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A phase II trial ( 90 ) and subsequent study from Redmond et al demonstrated that conformal avoidance of the hippocampus during WBRT/PCI was associated with improved memory and QoL, with only 10% of patients developing new BM in the underdosed area, which were amenable to stereotactic radiosurgery (SRS) ( 59 , 90 ). The recently completed phase III PREMER-TRIAL also demonstrated that compared to conventional PCI, hippocampal avoidance PCI improved free delayed recall at 3 months (21.7 vs. 5.1%), 6 months (32.6 vs. 7.3%), and 12 months (18.5 vs. 3.8%) ( 91 ). These encouraging results have led to the development of NRG-CC003, an active, randomized phase II/III trial of WBRT with or without hippocampal avoidance in patients with both LS-SCLC and ES-SCLC (NCT02635009).…”
Section: Future Directions Of Radiotherapy In Sclcmentioning
confidence: 99%
“…A phase II trial ( 90 ) and subsequent study from Redmond et al demonstrated that conformal avoidance of the hippocampus during WBRT/PCI was associated with improved memory and QoL, with only 10% of patients developing new BM in the underdosed area, which were amenable to stereotactic radiosurgery (SRS) ( 59 , 90 ). The recently completed phase III PREMER-TRIAL also demonstrated that compared to conventional PCI, hippocampal avoidance PCI improved free delayed recall at 3 months (21.7 vs. 5.1%), 6 months (32.6 vs. 7.3%), and 12 months (18.5 vs. 3.8%) ( 91 ). These encouraging results have led to the development of NRG-CC003, an active, randomized phase II/III trial of WBRT with or without hippocampal avoidance in patients with both LS-SCLC and ES-SCLC (NCT02635009).…”
Section: Future Directions Of Radiotherapy In Sclcmentioning
confidence: 99%
“…Given the importance of the PCI question to the majority of SCLC patients without brain metastases at diagnosis, MAVERICK is a pragmatic trial designed to minimize barriers to accrual allowing varying and evolving SCLC practice patterns including immunotherapy, consolidative thoracic radiation for ES-SCLC, HA-PCI, memantine, and salvage therapies including WBRT, HA-WBRT, and SRS at the discretion of the treating physician. This trial is supported by a recent patterns of care survey amongst 487 radiation oncologists which reported that routine recommendation for PCI in ES-SCLC had dropped from 72% to 44% following the Japanese trial, and that 82% of respondents would be willing to enroll patients with either LS and/or ES SCLC on a trial comparing MRI surveillance with and without PCI (42)(43)(44). An important design feature of the MAVERICK trial is the prerandomization stratification by LS-SCLC and ES-SCLC which will ensure balance between the arms while allowing investigators to enroll the patients with the stage of SCLC for which they have equipoise on the PCI question (i.e., LS-SCLC, ES-SCLC, or both).…”
Section: New Phase III Trial and Future Directionsmentioning
confidence: 80%
“…The phase II portion of NRG CC003 was designed to determine whether the 12-month intracranial relapse with HA-PCI was non-inferior to standard PCI, and the ongoing phase III component is designed to determine whether HA-PCI can reduce the likelihood of 6-month cognitive deterioration on the Hopkins Verbal Learning Test-Revised (HVLT-R). Of note, prior smaller randomized trials of PCI vs. HA-PCI have returned conflicting results regarding the cognitive impact of HA-PCI (42,43).…”
Section: Toxicity and Risk Mitigation Of Pcimentioning
confidence: 99%
“…Although two patients (10% of their cohort) developed metastasis in an under-dosed brain region, the tumors were effectively treated with SRS. De Dios et al also reported that the PCI group showed a significant decline in memory compared to the HA-PCI group 17 . Moreover, a recent randomized phase III trial suggested that there was no significant difference in the incidence of brain metastases between standard PCI and HA-PCI according to their abstract 18 .…”
Section: Discussionmentioning
confidence: 91%